Applications for the Disabled People with Health Limitations and Old People - I. POPOV, E. (International Journal of Engineering and Technology, 2018)
Currently, there are various specialized devices that make life easier for people with limited mobility, the disabled, and the elderly. It should be borne in mind that a modern mobile phone or tablet with special applications installed on it can, if not replace, complement these devices, making life easier for deaf, hard of hearing, blind, visually impaired people, and autists. Some versions of the considered applications are accessible from a computer using a browser. If desired, you can install the android emulator on your computer and run some of the programs reviewed. This research has considered applications created to make life easier for people with disabilities, people with health limitations and the elderly.Â Â Â